If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+12/3*7=x
We move all terms to the left:
1+12/3*7-(x)=0
We add all the numbers together, and all the variables
-1x+1+12/3*7=0
We multiply all the terms by the denominator
-1x*3*7+12+1*3*7=0
We add all the numbers together, and all the variables
-1x*3*7+33=0
Wy multiply elements
-21x*7+33=0
Wy multiply elements
-147x+33=0
We move all terms containing x to the left, all other terms to the right
-147x=-33
x=-33/-147
x=11/49
| -4(5+2h)=22 | | g-3/7=3/2 | | 10=3(m+1)+1 | | h+2=10+5h | | 15=3-n | | -b-10=10-5-4b | | 5(d-73)-23=37 | | 9=2(n+3)+1 | | 0=-2(k+1) | | q-10=8+4q | | 2(h+1)+6=16 | | 10h/2=3 | | 17-u=14 | | 760=x²+18x | | 3(t+16)=18 | | 760=x^2+18x | | 6t=5t+4 | | 1/n=-1 | | H=t+4 | | 3(j-9)+1=19 | | 2(d-11)-4=4 | | k(7k+2)=5 | | 14x+64=6x-64 | | 16=12z-100 | | 12x+32=-6x-32 | | x-5=+2 | | 3p+1=9+4p | | 9x-35=6x+43 | | 3*j=27 | | 24n=22 | | 24=22n | | 3x+6+153=180 |